2006
DOI: 10.1248/bpb.29.64
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic Acid Inhibits Compound 48/80-Induced Allergic Symptoms in Mice

Abstract: Caffeic acid (3,4-dihydroxycinnamic acid), one of the moieties of chlorogenic acid, is a phenolic compound widely distributed in plant materials other than coffee, including vegetables and fruits.1) Some biological effects have been attributed to caffeic acid. Huang et al.2) have reported the inhibitory effects of chlorogenic and caffeic acid on 12-Otetradecanoylphorbol-13-acetate-induced tumors in mice. Furthermore, the anti-inflammatory properties of caffeic acid and its derivatives have been proven in in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 21 publications
1
23
0
1
Order By: Relevance
“…MMBP may contain biologically active compounds such as caffeic acid and flavonoid derivatives. Thus, considering the conclusions of previous reports, 12,13) we believe that MMBP has antiallergy effects. On the other hand, it is clear that the compounds obtained from caffeic acid derivatives in MMBP have strong antioxidant activity.…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations
“…MMBP may contain biologically active compounds such as caffeic acid and flavonoid derivatives. Thus, considering the conclusions of previous reports, 12,13) we believe that MMBP has antiallergy effects. On the other hand, it is clear that the compounds obtained from caffeic acid derivatives in MMBP have strong antioxidant activity.…”
Section: Resultssupporting
confidence: 53%
“…In the study, caffeic acid was administered to rats in doses of 200 and 500 mg/ kg, and the administration of only 500 mg/kg was effective. 13) In the present study, MMBP was effective against vascular permeability at a dose of only 200 mg/kg. Therefore it is suggested that the vascular permeability inhibition of MMBP was more effective than that of caffeic acid.…”
Section: Resultsmentioning
confidence: 42%
See 2 more Smart Citations
“…9,13,21) Recent study indicated that CA had anti-inflammatory effects by reducing MPO activity and phospholipase A 2 activity in skin-incised mice. 14) However, the mechanisms underlying the anti-inflammatory effects of CA in skin inflammation are only partially understood.…”
Section: Discussionmentioning
confidence: 99%